Primary Epithelioid Angiosarcoma of the Thyroid in a Patient Occupationally Exposed to Radiations - Marina, Michela; Corcione, Luigi; Serra, Maria Francesca; Ferri, Teore; Silini, Enrico Maria; Ceresini, Graziano (Frontiers in Endocrinology, 2018)
Epithelioid angiosarcoma (EAS) of the thyroid is a rare and very aggressive tumor. Its incidence is higher in iodine-deficient areas but cases unrelated to endemic goiter have also been reported. We describe a case of a 63-year-old Italian man living in a non iodine-deficient area and with no previous diagnosis of goiter who came to the clinical observation because of the rapid onset of dyspnea and dysphonia. The patient was an interventional cardiologist who had worked for fifteen years in an angiographic room. Computed tomography (CT) showed a 13-cm inhomogeneous neck mass, originating from the left thyroid lobe which caused displacement and stenosis of the trachea. The patient underwent diagnostic fine-needle aspiration that was followed by total thyroidectomy plus central compartment and left lateral lymphadenectomy. The final pathological diagnosis was epithelioid angiosarcoma, high grade. The preoperative staging by CT of the head, neck, abdomen, chest and pelvis was negative. At pathological staging, the tumor was limited to the thyroid and no lymphnode metastases were detected. Chemotherapy with Epirubicin and Ifosfamide was administered for 4 cycles and then interrupted due to significant bone marrow toxicity. One year after diagnosis, the CT of neck, abdomen, chest and pelvis were negative. At two years after diagnosis, the FDG-PET was negative with no evidence of the disease at the CT follow-up. The patient is still alive at 62 months after diagnosis. He is on a follow-up program by a 6-month /1-year neck, chest, abdomen, and pelvis CT evaluation with no signs of metastases.